The Affinities - Wilson, Robert Charles, 1953- (Tor, 2015)
After becoming a part of the Tau, one of twenty-two large global network Affinities in the near future, young Adam Fisk thinks his life has improved for the better until the different Affinities begin to go to war with one another -- in a conflict that will change Adam's world forever.